Inclusion of renewable energy in electricity markets and its impact on price and energy security (2017)
There is a need for a reduction in greenhouse gases emissions, with the associated challenges for control and understanding across different stakeholders. In particular, the electricity sector is key to stand against such emissions. The transition from fossil fuel to renewable energies, mainly wind and solar, is being encouraged across the globe as sources of green electricity generation, supported by the agreements achieved in the Kyoto protocol and, recently, in Paris agreement. In recent years, the investment costs of renewable energy have fallen at competitive levels in some cases, which along with different incentives, there is a rise in the renewable installed capacity. The inclusion of these resources in the electricity matrix and the electricity market entails great challenges and uncertainty, because these resources, wind and solar, depend of seasonal weather conditions to generate energy, such as wind and radiation, respectively. Thus, such variation introduces new challenges, would renewable energy variation jeopardise security of supply in electricity markets? In this thesis is developed a behavioural simulation model, based on the System Dynamics methods for a simulation analysis considering alternatives scenarios. Different mixes of renewable sources bring with issues about the generation, as well as the economic dispatch due to the uncertainty associated to intermittence of renewable resources. On the one hand, intermittency requires controlling and monitoring by market operator to guarantee the energy demanded hour by hour since a weather variation can change the merit order dispatch, calling for conventional generator to supply energy missing. On the other hand, a high participation of renewable resources implies a low spot price due to zero variable costs which reduce profitability of conventional firm in short time and closure the firms in the middle term and long term, lowing the capacity margin. All previous have impact in the price stability, generate uncertainty on energy generation and dispatch, and potential strong negative effect in security of supply. In this thesis, a dynamic hypothesis associated to the electricity market -represented by the causality among system variables- is presented. The results pave the way towards better decision-making by authorities in order to solve latencies associated to the system